2009
DOI: 10.1002/adma.200802441
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Crystalline ZnS Nanobelts as Ultraviolet‐Light Sensors

Abstract: Single‐crystalline ZnS nanobelts with sharp ultraviolet‐light emission (∼337 nm) at room temperature have been assembled as UV Sensors. The high spectral selectivity, combined with high photosensitivity and fast response time, justifies the effective utilization of the present ZnS nanobelts as “visible‐light‐blind” UV photodetectors in different areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
416
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 548 publications
(432 citation statements)
references
References 42 publications
13
416
2
1
Order By: Relevance
“…Interstitial sulfur atoms are formed through the decomposition of H 2 S, as shown in reaction (2). And sulfur vacancies appear in ZnS because of reaction (3). As a result, ZnS-873 and ZnS-973 may contain little sulfur vacancies while interstitial sulfur and sulfur vacancies might coexist in ZnS-1073 and ZnS-1173 particles.…”
Section: Structure and Morphology Of Zns Nanocrystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interstitial sulfur atoms are formed through the decomposition of H 2 S, as shown in reaction (2). And sulfur vacancies appear in ZnS because of reaction (3). As a result, ZnS-873 and ZnS-973 may contain little sulfur vacancies while interstitial sulfur and sulfur vacancies might coexist in ZnS-1073 and ZnS-1173 particles.…”
Section: Structure and Morphology Of Zns Nanocrystalsmentioning
confidence: 99%
“…Tailoring the color output of nanomaterials is very important for their applications as light emitting displays, field emitters, 1,2 lasers, sensors 3 and optoelectronic devices to multiplexed biological labeling. [4][5][6][7] Zinc sulfide (ZnS) is a suitable semiconductor as a host matrix for a wide variety of dopants on account of its wide energy band gap.…”
Section: Introductionmentioning
confidence: 99%
“…A typical I-V curve for the twoterminal structure under an EBI (10 keV), as shown in Figure 3b, indicates that the irradiation-induced current can reach 9.5 pA with a bias of 25 V. It was also found that the dark current was beyond the current meter's detecting limit (10 − 14 A); these results are in agreement with the published results in the literature. 24 By switching the electron beam on and off, the device showed a good repeatability (Figure 3c) and fast response (o1 s), as determined from the enlarged portions of the rise and fall in Supplementary Figure S5. In this study, these twoterminal devices cannot be completely turned off; however, a residual current was detected as a result of the high-energy irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…Among these, semiconductors are the most excellent material showing appreciable modification in the optical and electronic properties through the alteration in the energy band gap via doping with other foreign metals. Recently semiconducting nanocrystalline materials have immensely attracted the interest in electronics and photonics application [1] such as light emitting diodes [2], photonics [3], chemical, biological and UV sensors [4], phosphors in displays and also in biomedical applications for biological labelling [5], diagnostics [6].…”
Section: Introductionmentioning
confidence: 99%